Endogeneity Problem in Corporate Finance: Theory and Practice - Z. V. Selezneva; M. S. Evdokimova (Финансы: теория и практика)
Endogeneity can cause a significant bias in the coefficient estimation, up to the change in sign. It leads to controversial research results, which also makes it difficult to adequately test individual hypotheses and theories in corporate finance (CF). For practitioners, such as company valuation consultants, these model problems interrupt obtaining the most reliable estimates in the interests of the customer. The aim of this study is to review an endogeneity problem in CF and ways to solve a problem of endogeneity. We will illustrate the methods found in the systematic review with an empirical example. The paper provides the reasons for this problem from an econometric point of view and with examples from the CF and econometric methods of dealing with it. As a result of a systematic literature review, we have shown that dynamics panel models, in particular the Blundell-Bond method, are mostly used to consider endogeneity in CF studies. We have verified empirically the conclusion made in the framework of the literature review. To detect the endogeneity, we used the Hausman test, the endogeneity test, and the analysis of the correlation matrix, including the saved regression residuals. Eliminating step-by-step endogeneity, we concluded that the Blundell-Bond method is not always the optimal one for dealing with endogeneity in CF, as well as regression with a fixed effect. It was revealed that the two-stage least squares method (IV 2SLS) is the most appropriate method for the cost of capital model estimation eliminating endogeneity. In addition, the estimates of the cost of capital model, which analyzes the impact of non-financial reporting, have been improved.